2012
DOI: 10.5194/amt-5-2361-2012
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing of ice crystal asymmetry parameter using multi-directional polarization measurements – Part 1: Methodology and evaluation with simulated measurements

Abstract: Abstract. We present a new remote sensing technique to infer the average asymmetry parameter of ice crystals near cloud top from multi-directional polarization measurements. The method is based on previous findings that (a) complex aggregates of hexagonal crystals generally have scattering phase matrices resembling those of their components; and (b) scattering phase matrices systematically vary with aspect ratios of crystals and their degree of microscale surface roughness. Ice cloud asymmetry parameters are i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 88 publications
(126 reference statements)
3
79
0
Order By: Relevance
“…The abundance of small ice particles may be due to the shattering of large ice particles on the probe inlet, artificially increasing the number of small particles seen in the images (Korolev et al, 2011). Compact aggregates and spatial bullet rosettes are also seen and tend to be more common in the midlatitudes (Um and McFarquhar, 2007). Some of the particles observed by the CPI probe appear to have hollow structures, a feature noted by Magono and Lee (1966), Schmitt and Heymsfield (2007), Baran (2012), and Yang et al (2008c, specifically, the photograph by Steven Warren shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The abundance of small ice particles may be due to the shattering of large ice particles on the probe inlet, artificially increasing the number of small particles seen in the images (Korolev et al, 2011). Compact aggregates and spatial bullet rosettes are also seen and tend to be more common in the midlatitudes (Um and McFarquhar, 2007). Some of the particles observed by the CPI probe appear to have hollow structures, a feature noted by Magono and Lee (1966), Schmitt and Heymsfield (2007), Baran (2012), and Yang et al (2008c, specifically, the photograph by Steven Warren shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Surface roughness has been observed in laboratory measurements of ice and from in situ measurements obtained in field campaigns (Korolev et al, 2011;Um and McFarquhar, 2007;Baumgardner et al, , 2011Neshyba et al, 2013). Thermodynamic conditions influence whether an ice particle is roughened and how rough it becomes (Baran et al, 2011), but it is currently unknown what percentage of ice particles in clouds might be roughened or how rough they are.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the formalism is recognized to model the total reflectance with sufficient accuracy for reasons likely associated with the large number of scattering events taking place within the snowpack. Based on this assumption, the method is expected to perform even better for the polarization component because the polarimetric signatures of a medium are known to originate from its top layer (van Diedenhoven et al, 2013): deeper into the medium (i.e., past the first units of optical depth) multiple scattering randomizes polarization.…”
Section: Introductionmentioning
confidence: 99%